Brand equity analysis to increase health care utilization - Ernawaty; Kendra Wardhani K; Stefanus Supriyanto; Nuzulul Kusuma Putri; Yeni Rahmah Husniyawati (SAGE Publishing, 2020)
Background: Health care utilization is one of the key indicators in measuring performance of health care services. Strong brand equity suggests positive correlation with great attraction for consumers to use a product. Design and Methods: A cross-sectional study was conducted to identify the effects of brand equity to health care utilization. 381 students were selected by simple random sampling. Multiple logistic regression tests were used to analyze the influence between variables. Results: Findings showed that there was an influence between brand equity and health care utilization (P=0.001). In the three attributes, brand equity was known to have an influence to the utilization of health care. The highest influence of the three attributes was brand association (Exp (B) = 2.501). Conclusions: It can be concluded that brand equity affects patient visits to AHCC showing that the brand equity significantly influence patient visits. Promotion to create familiarity and good impression was required to enhance brand equity and increase health care utilization.